THE PATHWAY OF CHEMICAL EVOLUTION IN BEARDED IRIS SPECIES BASED ON FLAVONOID AND XANTHONE PATTERNS - WILLIAMS, C.A.; HARBORNE, J. B.; COLASANTE, M. (Annali di Botanica, 2000)
Four diploid and seven allopolyploid bearded Iris were surveyed for their leaf flavonoid, isoflavonoid and xanthone constituents in order to investigate their phylogeny. Eighteen flavone Cglycosides and eight C-glucoxanthones were identified and proved to be useful evolutionary markers. The phenolic data showed that Iris pseudopumila was a strong candidate as a diploid parent of some allopolyploid taxa e.g. I. marsica and I. lutescens but rules out the participation of I. pallida. Amongst the 2n = 44 allopolyploids the results suggested that I. germanica and I. albicans are very closely related and that they have evolved from the 2n = 40 taxa e.g. I. bicapitata.